Предмет: Алгебра,
автор: Regina800
решите уравнение (4x+3)(x-1)-(3x-2)(x+2)=10-5x
Ответы
Автор ответа:
1
(4х + 3)(х-1) - (3х - 2)(х +2) = 10 - 5х
4х² - 4х + 3х - 3 - (3х² +6х - 2х - 4) = 10 - 5х
4х² - х - 3 - (3х² +4х -4) = 10 - 5х
4х² - х - 3 - 3х² - 4х + 4 = 10 - 5х
(4х² - 3х²) -(х+4х) + (4-3) = 10 - 5х
х² - 5х + 1 = 10 - 5х
х² - 5х + 1 - 10+ 5х = 0
х² + (5х - 5х) - (10 - 1) = 0
х² - 9 = 0
х² = 9
х₁ = √9
х₁ = 3
х₂ = -√9
х₂ = - 3
4х² - 4х + 3х - 3 - (3х² +6х - 2х - 4) = 10 - 5х
4х² - х - 3 - (3х² +4х -4) = 10 - 5х
4х² - х - 3 - 3х² - 4х + 4 = 10 - 5х
(4х² - 3х²) -(х+4х) + (4-3) = 10 - 5х
х² - 5х + 1 = 10 - 5х
х² - 5х + 1 - 10+ 5х = 0
х² + (5х - 5х) - (10 - 1) = 0
х² - 9 = 0
х² = 9
х₁ = √9
х₁ = 3
х₂ = -√9
х₂ = - 3
Похожие вопросы
Предмет: Геометрия,
автор: nastyakoza08
Предмет: Алгебра,
автор: momol35
Предмет: История,
автор: varyaszww
Предмет: Математика,
автор: Vovka1231
Предмет: Литература,
автор: ROMPEL2015